An assessment of the effectiveness of central bank sterilization on capital inflows in Nigeria - Tijjani M. Jume (CBN Journal of Applied Statistics, 2020)
This paper assesses the monetary policy response of the Central Bank of Nigeria(CBN) to increases in capital inflows into Nigeria using monthly time series datafrom January 2009 to December 2017. It presents an econometric assessment of thedegree to which the CBN sterilizes net foreign assets (NFA) in response to the cap-ital flows, using Autoregressive Distributed Lag (ARDL) Bounds testing approach.The long run sterilization coefficient obtained suggests that the CBN successfullyoffset 95per cent of capital inflows in the period of analysis. Against the back-ground of rising financial instability in Nigeria, the study illustrates how steriliza-tion has not adequately tackled the major risks of capital inflows which resultedin asset price bubbles and bursts, equity capital inflows reversal, banking crisis,and currency depreciation which contributed, partly, to the economic recession in2016. The paper argues that effective policy response to capital inflows must ade-quately address the major downside risks of capital inflows in the short and mediumterms through some clearly defined capital flows management and macro-prudentialmeasures.
Keywords: E52; E58; 330; Assets price; capital flows; impossible trinity; sterilization